The Bhutto Dynasty : The Struggle for Power in Pakistan - Bennett Jones, Owen (London Yale University Press, 2020)
A major new investigation into the Bhutto family, examining their influence in Pakistan from the colonial era to the present day.
Include Color Illustrations, Notes and Index
Keywords: Pakistan -- Bhutto Family -- Politics and Government -- HISTORY / Asia / India & South Asia